A construção jurídica da fortaleza Europa: da comunitarização das estratégias migratórias à emergência do sistema europeu de vigilância das fronteiras (Eurosur) - Machado, Sadi Flôres (2015)
The gradually communitisation of migration policies in the European Union (EU) coincides with the increase of human flows in the Schengen area, driven largely by the characteristics and economic demands of the global network society. In this process, the tension is deposited between the need for Community harmonization in the embryonic foundations of a principle of solidarity aimed at protecting humanana mobility ("Europe without borders") and the effective adoption of legal acts sustained by the security perception of migration ("Fortress Europe"). Under such assumptions, the research analyzes the communitarisation process of selective migration policies (refoulement of irregular immigrants and attracting highly skilled workers) and the emergence of immigration restriction techniques (technological surveillance of external borders and landless of migration control), with special Featured establishing a European Border Surveillance System (EUROSUR). We opted for the dialectical-inductive approach to the topic in order to suit the analysis of the intertwining of migration policies, normative acts and judicial decisions and their itineraries and contextual contradictions. As for the procedure, especially the monographic methods were used, historical, comparative and case study. It investigates how human mobility in Europe fall within the overall context of migration, through the analysis of normative sources devoted to ticket management and national residence of third countries in the EU, with the purpose of gauging how is the division of powers on migration. We analyze also the human rights guaranteed to migrants through the jurisprudence of the European Court of Human Rights (ECHR) and the Agency's reports of the European Union Fundamental Rights (EU). Community Directives were analyzed related to the co-optation of qualified immigrants and immigrant repulsion undocumented, featured reflections of the security obsession that marks the European migration strategies. Finally, it approaches the implementation of EUROSUR, relating to the consolidation of surveillance as an emerging paradigm in the global legal scenario. Finally, it is concluded that the regional management of migration under the logic of selectivity by giving a Community surveillance, accelerates economic crises in countries of origin, increasing the volume of mobility towards the destination countries.